2021
DOI: 10.3390/molecules26092408
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and Antilipidemic Properties of a Tea Infusion of the Leaves from Annona cherimola Miller on Streptozocin-Induced Type 2 Diabetic Mice

Abstract: The antihyperglycemic and antilipidemic effects of the tea infusion extracts of leaves from Annona cherimola Miller (IELAc-0.5, IELAc-1.5, and IELAc-3.0) were evaluated on normoglycemic (NG) and streptozocin-induced diabetic (STID) mice. In the acute test, IELAc-1.5 at 300 mg/kg bodyweight (bw) exhibited antihyperglycemic activity on STID mice since the first hour of treatment. Then, its antidiabetic potential was analyzed in a subchronic evaluation. IELAc-1.5 was able to reduce the blood glucose level, glycat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 67 publications
0
22
0
3
Order By: Relevance
“…The aqueous extracts of Annona muricata , A. stenophylla , and A. macroprophyllata have shown antidiabetic, antioxidant, antilipidemic, and antinociceptive effects that are attributed to the presence of phenolic compounds in their leaves [ 34 , 35 , 36 , 37 ]. The antidiabetic properties of extracts from Ac have also been studied in previous publications [ 25 ] and it has been established that making a tea infusion from the leaf powder is a good way to produce the antilipidemic effect [ 38 ]; therefore, this extract was used in the present study. Nevertheless, no reports showing the histological changes induced by the treatment with this extract or changes in the effect related to the harvest period of the leaves have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extracts of Annona muricata , A. stenophylla , and A. macroprophyllata have shown antidiabetic, antioxidant, antilipidemic, and antinociceptive effects that are attributed to the presence of phenolic compounds in their leaves [ 34 , 35 , 36 , 37 ]. The antidiabetic properties of extracts from Ac have also been studied in previous publications [ 25 ] and it has been established that making a tea infusion from the leaf powder is a good way to produce the antilipidemic effect [ 38 ]; therefore, this extract was used in the present study. Nevertheless, no reports showing the histological changes induced by the treatment with this extract or changes in the effect related to the harvest period of the leaves have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a dose of 100 mg/kg of both methanolic extract and the residual fractions of A. reticulata leaves decreased blood glucose levels from 432.33 to 371.67 mg/dL and 417.83 to 402.50 mg/dL, respectively, in streptozotocin-induced diabetic rats [ 181 ]. A. cherimola leaf extract was also found to decrease HbA1c by 7% and lead to a significant decrease in urine glucose over a 28-day subchronic study in streptozotocin-induced diabetic mice [ 182 ]. These studies support the traditional use of Annona species as antidiabetics, suggesting that further identification of the active constituent(s) with antidiabetic properties and clinical studies of a longer duration are warranted.…”
Section: Pharmacological Properties Of Annona Speciesmentioning
confidence: 99%
“…Administration of an extract of A. muricata extracts resulted in reductions in the serum total cholesterol, low-density lipoprotein cholesterol and triglycerides in diabetic rats [ 183 ]. The tea infusion of leaves from A. cherimola (1.5 g) also elicited a reduction in the total cholesterol, triglycerides, and low-density lipoprotein by 15.4, 21.9 and 63.2%, respectively, in streptozotocin-induced diabetic rats [ 182 ].…”
Section: Pharmacological Properties Of Annona Speciesmentioning
confidence: 99%
“…Various studies on anti-hyperglycemic effects are reported for Annona species. The anti-hyperglycemic activity of A. squamosa leaves, roots, and peel extracts have been evaluated in hyperglycemic or diabetic models [ 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. Table 4 shows that leaves have been studied more than other tissues.…”
Section: Agronomic Knowledgementioning
confidence: 99%